TAXPAYER ATTITUDE ON THE ELIMINATION OF TAX SANCTION AND TAXATION AWARENESS TOWARD TAXPAYER COMPLIANCE IN YOGYAKARTA - Suparna Wijaya (Jurnal Manajemen Indonesia, 2019)
The impact of tax on state revenue is very dominant these days. This happens because tax is a definite source in contributing funds to the state. Basically, it is a reflection of the mutual cooperation of the community in state financing regulated by legislation. One of the factors causing low taxpayer's compliance takes place because the public as taxpayers forget or maybe even simply ignore their obligation to pay taxes, especially personal income tax. This research is quantitative in nature, which involves testing hypotheses (explanatory). The population in this study is individual taxpayer registered at the Regional Office of the Directorate General of Taxes of the Special Region of Yogyakarta. Approximately 350,935 Individual Taxpayers at the end of 2015 were registered. The research results indicated a positive influence between the attitude of taxpayers and taxpayer's compliance. By contrast, with respect to taxpayer compliance, the analysis on tax elimination variable shows that there is no positive influence between the elimination of tax sanctions and taxpayer compliance. The analysis on tax awareness toward taxpayer compliance indicates a positive influence between tax awareness and taxpayer compliance. Keywords—Tax Awareness; Taxpayer Compliance; Individual Taxpayers; Taxpayer Attitudes. Abstrak Perananpajakterhadap pendapatan Negara sangat dominan pada masa sekarang ini.Ini terjadi karena pajak adalah sumber yang pasti dalam memberikan kontribusi dana kepada Negara karena merupakan cerminan dari kegotongroyongan masyarakatdalam pembiayaan negara yang diatur oleh perundang-undangan. Salah satu factor menyebabkan penerimaan pajak yang sulit tercapai yaitu kepatuhan wajib pajak yang rendah itu dibuktikan karena masyarakat selaku wajib pajak lupa, atau bahkan mungkin mengabaikan kewajibannya untuk membayar pajak, khususnya pajak penghasilan orang pribadi. Jenis penelitian ini merupakan penelitian kuantitatif dengan melakukan pengujian hipotesis (eksplanatory). Populasi dalam penelitian ini adalah Wajib Pajak Orang Pribadi yang terdaftar pada Kantor Wilayah Direktorat Jenderal Pajak Daerah Istimewa Yogyakarta, kurang lebih berjumlah 350.935 Wajib Pajak Orang Pribadi pada akhir tahun 2015. Hasil penelitian menunjukkan terdapat pengaruh yang positif antara Sikap wajib pajak dengan kepatuhan wajibpajak, sedangkan untuk variable kepatuhan wajib pajak terhadap penghapusan pajak menunjukkan tidak terdapat pengaruh positif antara penghapusan sanksi pajak dengan kepatuhan wajib pajak dan untuk variable kesadaran perpajakan terhadap kepatuhan wajib pajak menunjukkan terdapat pengaruh positif antara kesadaran perpajakan dengan kepatuhan wajib pajak. Kata kunci—Kesadaran Perpajakan; Kepatuhan Wajib Pajak; Wajib Pajak Orang Pribadi; Sikap Wajib Pajak.